Biosystematics and evolution of the Triatominae - Christopher J. Schofield
In this paper we summarize the systematics of the 130 currently recognized species of Triatominae and the key features of their evolutionary background. There is increasing evidence that the subfamily has polyphyletic origins, with the various tribes and species groups probably arising from different reduviid lineages in relatively recent times.